Variable RBE in proton therapy: comparison of different model predictions and their influence on clinical-like scenarios - Giovannini, Giulia; Bauer, Julia; Tessonnier, Thomas; Debus, Jürgen; Mairani, Andrea; Parodi, Katia (Radiation oncology, 2016)
In proton radiation therapy a constant relative biological effectiveness (RBE) of 1.1 is usually assumed. However, biological experiments have evidenced RBE dependencies on dose level, proton linear energy transfer (LET) and tissue type. This work compares the predictions of three of the main radio-biological models proposed in the literature by Carabe-Fernandez, Wedenberg, Scholz and coworkers.
Gesehen am 10.09.2019